Dexmedetomidine-midazolam versus Sufentanil-midazolam for Awake Fiberoptic Nasotracheal Intubation： A Randomized Double-blind Study - Li, Cheng-Wen; Li, Yan-Dong; Tian, Hai-Tao; Kong, Xian-Gang; Chen, Kui (Chinese medical journal, 2015)
Background： Awake fiberoptic intubation （AFOI） is usually performed in the management of the predicted difficult airway. The aim of this study was to evaluate the feasibility of dexmedetomidine with midazolam （DM） and sufentanil with midazolam （SM） for sedation for awake fiberoptic nasotracheal intubation. Methods： Fifty patients with limited mouth opening scheduled for AFOI were randomly assigned to two groups （n = 25 per group） by a computer-generated randomization schedule. All subjects received midazolam 0.02 mg/kg as premedication and airway topical anesthesia with a modified ＂spray-as-you-go＂ technique. Group DM received dexmedetomidine at a loading dose of 0.5 μg/kg over 10 min followed by a continuous infllsion of 0.25 μg.kg^-1.h ^-1, whereas Group SM received sufentanil at a loading dose of 0.2 μg/kg over 10 rain followed by a continuous infusion of 0.1 μg.kg^-1.h ^-1. As necessary, since the end of the administration of the loading dose of the study drug, an additional dose ofmidazolam 0.5 mg at 2-min intervals was given to achieve a modified Observers＇Assessment of Alertness/Sedation of 2-3. The quality of intubation conditions and adverse events were observed. Results： The scores of ease of the AFOI procedure, patient＇s reaction during AFOI, coughing severity, tolerance after intubation, recall of the procedure and discomfort during the procedure were comparable in both groups （z = 0.572, 0.664, 1.297, 0.467, 0.895, and 0.188, respectively, P 〉 0.05）. Hypoxic episodes similarly occurred in the two groups, but the first partial pressure of end-tidal CO, after intubation was higher in Group SM than that in Group DM （45.2 ± 4.2 mmHg vs. 42.2 ±4.3 mmHg, t = 2.495, P 〈 0.05）. Conclusions： Both dexmedetomidine and sufentanil are effective as an adjuvant for AFOI under airway topical anesthesia combined with midazolam sedation, but respiratory depression is still a potential risk in the sufentanil regimen.